Newsletter No. 20 - (:unkn) unknown (My University, 2008)
Contains a brief summary of the LSAC 2006-2007 Annual report, availablility of Wave 2.5 data, information on Wave 3 interviewer workshops and Wave 4 development, data user training and the Special LSAC edition of Family Matters.
20
Newsletter
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology